2007
DOI: 10.1007/s00436-007-0627-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coccidia in beef cattle in western Turkey

Abstract: A total of 504 bovine faecal samples collected from intensively managed beef farms in Afyon province of Turkey were examined to determine the types and prevalence of coccidian parasites present. Coccidian oocysts were found in 20.04% of all the samples examined by sucrose-flotation. The species detected and their prevalence were Eimeria bovis (34.55%), E. auburnensis (23.03%), E. canadensis (14.55%), E. brasiliensis (10.91%), E. zuernii (6.67%), E. bukidnonensis (3.03%), E. cylindrica (2.42%), E. ellipsoidalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 13 publications
9
23
1
3
Order By: Relevance
“…We found 8 Eimeria and Isospora species which were also found in a study (Cicek et al 2007) carried out on cattle in the Afyon province, where we also performed our study. This shows that the species we found might be cattle-originated.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We found 8 Eimeria and Isospora species which were also found in a study (Cicek et al 2007) carried out on cattle in the Afyon province, where we also performed our study. This shows that the species we found might be cattle-originated.…”
Section: Resultssupporting
confidence: 86%
“…In our study the infection rate was 92.5% in animals younger than 1 year and 64.1% in animals older than 1 year. Infection rates were compatible with the study of Cicek et al (2007) regarding the effect of age on infection rates.…”
Section: Resultssupporting
confidence: 85%
“…A negative correlation exists between age of cattle and risk of infection. Younger animals depicted higher prevalence (27.23 %) of coccidial infection than older animals (15.65 %) as reported by Cicek et al (2007). Higher oocysts counts have been observed in immature as compared to adults (Waruiru et al 2000).…”
Section: Treatment and Discussionsupporting
confidence: 67%
“…After sporulation of positive samples in Koutny et al (2012) experiment, 11 Eimeria species were found. Ten different species of Eimeria were identified from the fecal samples of local domestic beef cattle collected from the five localities of Afyon province of Turkey (Cicek et al 2007). In Hungary Eimeria oocysts were found in 33% of calve and seven species were identified.…”
Section: Resultsmentioning
confidence: 99%